MENYELAMATKAN NASIB ANAK BANGSA DENGAN PENDIDIKAN ISLAM - Hasan Basri Tanjung (Edukasi Islami : Jurnal Pendidikan Islam, 2015)
Islamic education is a typical pattern of education and noble. Educators, methods, materials, media, environment, means, objectives and other elements of clear and accurate to be used as a model by anyone and anywhere. Islamic education appear grandeur of its purpose which is to make a good man. Good quality human being is determined by his outlook on life. When the pastures of his life in the form of religion, then it is a good man a good man according to his religion. In the Qur'an al-Karim, the position of the child mentioned in a different context and meaning. At least, four ranked at the same position in the child's quality of family life. First, qurrota a'yun the consolation careful eye conditioning (Al-Furqaan [25]: 74). Secondly, ziinatul hayatiddunya namely jewelery earthly life (Al-Kahf [18]: 46). Third, aduwwal lakum the enemy to thee (At-Taghaabun [64]: 14). Fourth, the slander trial or test (al-Anfal [8]: 28, and At-Taghaabun [64]: 15). For the first context suggests that blends hope and effort to get a goodly child, consolation heart, eye conditioning and later became the leader of the people. While the context of the second, third and fourth is a statement and a warning that firm and hard that some children will be jewelry, enemies and defamation, so that parents or teachers should do the strategy right in their child's education. Kata kunci: anak bangsa, pendidikan Islam